A rare case of lymph node infarction - Srujana, Shyamala; Srivani, Narala; Krishna, Lanka; Kumar, Odapally Shravan; Quadri, Syed SS. (International Surgery Journal, 2016)
Lymph node infarction refers to a syndrome of coagulative necrosis of lymph node that is frequently associated with concurrent or subsequent development of malignant lymphoma. Lymph node infarction is a very rare entity among the various pathologies involving the lymph node. We hereby present a case report of lymph node infarction in a 40 year old female patient who presented with sub mandibular swelling.